(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Natural radioactivity is ubiquitous in the environment mainly due to the presence of the nuclides from the uranium and thorium series and 40K. Although in the South Hemisphere nuclear tests have been fewer in number than that in the North, artificial radionuclides can also be found spread at ground level. In this study, the activity concentrations of natural nuclides from the uranium and thorium series, 40K and the artificial 137Cs were determined in a sediment core with 42 cm depth collected in the middle of the Salesópolis reservoir, located in the Metropolitan Region of São Paulo city (SPMR). The Usina Parque Rio Tietê reservoir belongs to the Alto do Tietê system for the capture, storage and treatment of water for SPMR. Therefore, the quality of the water and sediments of this dam is of great importance. The activity concentrations were measured by gamma spectrometry. Samples were measured and saved at regular intervals at a maximum of 160 000 seconds. The gross area were determined for each peak and plotted against time and the counting rate was obtained by the slope of the curve. Background and reference materials were also counted and treated in the same way. Results showed that 226Ra varied from 45 to 116 Bq kg-1; 228Ra, from 80 to 165 Bq kg-1; 40K, from 155 to 1 187 Bq kg-1 and 137Cs varied from 0.3 to 7 Bq kg-1. The methodology applied for determining low levels of 137Cs in sediment proved to be efficient and reproducible.